Enterprise and organizational modeling and simulation : 12th International Workshop, EOMAS 2016, held at CAiSE 2016, Ljubljana, Slovenia, June 13, 2016, selected papers /: 12th International Workshop, EOMAS 2016, held at CAiSE 2016, Ljubljana, Slovenia, June 13, 2016, selected papers. (2016) - Unknown
No abstract available